An Analysis on Importance of Human Resource Accounting Practices in Various Indian Industrial Sectors: The Value of Human Resource Accounting in Indian Industrial Sectors (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Accounting is a man-made art and its principles and procedures have been evolved along period of time to aid business in reporting for management and public. Most of the literature in the discipline of accounting is so far concentrated on the aspects of physical and financial resources, which are well, accounted universally with accepted standards of preparation and presentation. Human resource is the energies, skills, talents and knowledge of people, which could be utilized and converted into the production of goods or rendering of useful services without human resources, the other resource cannot be operationally effective. “People are the most important asset of an organization yet, the value of this asset does not appear in the financial statements. This information has not even been included as a part of internal accounting and reporting for management purpose”.Human Resource Accounting (HRA) includes all these human resource information in the financial statements. Hence, the success of this organization is contingent on the quality of their human resource such as knowledge, skills, competence, motivation and understanding of the organizational culture, which are used to build and support these human aspects, so Human Resource Accounting (HRA) denotes just this process of quantification measurement of the human resource. In today's competitive world, human resource in organizations is one of the factors that can create competitive advantage for organizations. Effective and efficient use of human resources should be developed and accurate information is needed to managers for decision-making.